2016
DOI: 10.3233/nre-161341
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Induced Aphasia Therapy: Volunteer-led, unconstrained and less intense delivery can be effective

Abstract: Abstract.BACKGROUND: Constraint Induced Aphasia Therapy (CIAT) has been shown to be effective in the treatment of aphasia, but clinicians have expressed concern regarding how far CIAT is practical to implement in clinical practice. OBJECTIVE: To determine whether CIAT delivered in a less-intense, lower dose, reduced constraint and volunteer-led format could produce positive outcomes in people with chronic aphasia. METHODS: Two groups were run, each with two people with chronic aphasia. Treatment involved a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Usually, CIAT was delivered via a therapeutic group. Also, literature provided the evidence about the feasibility of trained laypersons-given CIAT [ 41 ], thus, an increasingly number of studies have introduced trained students or volunteers into the therapeutic groups [ 30 , 36 ], which make it more feasible in rehabilitation settings by saving the human powers. Moreover, recent studies showed that the CIAT implemented at acute phase and subacute phase [ 27 , 31 , 35 ] was tolerable by stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, CIAT was delivered via a therapeutic group. Also, literature provided the evidence about the feasibility of trained laypersons-given CIAT [ 41 ], thus, an increasingly number of studies have introduced trained students or volunteers into the therapeutic groups [ 30 , 36 ], which make it more feasible in rehabilitation settings by saving the human powers. Moreover, recent studies showed that the CIAT implemented at acute phase and subacute phase [ 27 , 31 , 35 ] was tolerable by stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study compared the CIAT-distributed (constraint and low intensity) and conventional therapy (unconstraint and low intensity), and showed no statistical difference in any outcomes [ 35 ]. Some studies with pre-post design reported the effect of less constraint or unconstraint [ 36 , 37 ]. However, the effect from constraint was found by some study, for example, a case study comparing with constraint and unconstraint therapy, the language performance was in favor of constraint group, which also was associated with the change in fMRI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively discouraging alternative forms of communication such as gestures does not seem crucial. Relatively unconstrained versions of CIP (where gestures are not prevented) have also been found to be effective (Difrancesco et al, 2012;Nickels & Osborne, 2016;Stahl, Mohr, Dreyer, Lucchese, & Pulvermüller, 2016) and as effective as constrained versions (Kurland, Pulvermüller, Silva, Burke, & Andrianopoulos, 2012). Moreover, a positive impact of gesture on naming has been noted by some studies (Frick-Horbury & Guttentag, 1998;Morsella & Krauss, 2004;Rose, 2013).…”
Section: Background and Rationalementioning
confidence: 95%
“…These protocols share the following defining characteristics: (1) Treatment is delivered in small groups (up to three patients); (2) practice is strictly focused on a verbal, spoken output with other forms of communication either not practiced or actively discouraged (constrained); (3) treatment is intensive where intensity refers to the therapy being delivered both with a high-dose and in a compact way (massed rather than distributed practice); (4) treatment is focused on word production (picture naming); (5) treatment involves shaping, where word production is practiced repeatedly, with different carrier sentences, and different degrees of facilitation; (6) naming is promoted in the context of social requests as part of a card game (Go Fish) where participants ask other participants for matching cards. CIP have received a lot of attention because studies have shown benefits for treated words and, occasionally, improvements on standardized tasks (e.g., Carpenter & Cherney, 2016;Pulvermüller et al, 2001; for a review, see Zhang et al, 2017; but also see for negative results-Attard, Rose, & Lanyon, 2012;Hameister, Nickels, Ca, & Croot, 2017;Kurland, Stanek, Stokes, Li, & Andrianopoulos, 2016;Nickels & Osborne, 2016). Which elements are responsible for the success of CIP, however, remain unclear.…”
Section: Background and Rationalementioning
confidence: 99%